Carrera de Turismo y Hotelería UEB tuvo presencia en el I Seminario Internacional - García García, Mariana (2023)
UNIT OF COMMUNICATION PRESS RELEASE 060 Guaranda, June 21, 2023 Tourism and Hospitality Career UEB was present at the I Seminar International With more than 1000 participants, the MSc exhibition was a complete success. Ainhoa Carballido-Risco, from the University of Barcelona - Spain, at the International Seminar organized by #FACAGEI, his presentation was about the design of experiences sustainable tourism, capturing the interest of the audience in the topic of relevance to the Tourism and Hospitality degree at the UEB.